Pengaruh Kewajiban Kepemilikan NPWP Berstatus PKP, Pemeriksaan Pajak, Penagihan Pajak, dan Kepatuhan Wajib Pajak terhadap Penerimaan Pajak Penghasilan Badan pada Kantor Pelayanan Pajak Pratama di Wilayah Kabupaten Ngawi - Andira Amalia Faradila; Hedi Pandowo; Koerniawan Dwi Wibawa (Asosiasi Riset Ekonomi dan Akuntansi Indonesia, 2024)
Income tax is one of the tax revenues whose revenues dominate tax revenues at KPP Pratama Ngawi, one of which is corporate income tax. The purpose of this study is to test the influence of ownership of Taxpayer Identification Number (NPWP) with PKP status, tax checking, tax collection and taxpayer compliance with corporate income tax revenue. The 4 variables studied include ownership of the Taxpayer Identification Number (NPWP) with PKP status, tax checking, tax collection and taxpayer compliance as independent variables and corporate income tax revenue as a dependent variable. This study was tried at the Primary Tax Service Office located in the Ngawi area. The study employs multiple linear regression analysis as well as hypothesis testing. The data used comes from primary data. The procedure for taking illustrations used is purposive sampling with illustration measurements using the formula slovin alpha 10%. The results of the study show that the obligation to own an NPWP with PKP status, Tax Collection, and Taxpayer Compliance have a significant negative effect on Corporate Income Tax. On the contrary, Tax Checking has a significant positive influence on Corporate Income Tax. Regarding this, it means that if it continues to be many tax auditors check taxes until corporate income tax revenues continue to increase